RADICALISM IN INDONESIA AND THE REFLECTIVE ALTERNATIVES TO REDUCE - Ibrahim, Ibrahim; Wulansari, Dini; Hidayat , Novendra (PEOPLE: International Journal of Social Sciences, 2018)
Radicalism has been an important issue in Indonesia since the last few decades. Identity exclusivity, mainly religion, has caused the increasing of radicalism potency in term of its inter-citizen relation. In order to solve the problem, it is needed contra-radicalism and de-radicalization strategies. In this case, contra-radicalism is carried out by immigration restriction, early detection, law enforcement, and organizations control. Meanwhile, deradicalization can be executed through education inclusive approach; leader persuasion, Pancasila socialization expansion, and religion position understanding straighten out. In addition, it needs to strengthen the citizenship principles, and encouraging the politics of welfare.